Ultrasound May Help Detect Chest Wall Recurrence After Mastectomy at an Early Stage. (21st May 2020) - Wang, Ying; Liu, Danru; Wu, Zhifeng
Abstract : Objectives: To define ultrasound (US) features that help diagnose local recurrence (LR) and differentiate benign masses from LR chest wall masses after mastectomy in patients with breast cancer. Methods: The US and surgical records of 119 pathologically confirmed chest wall masses in 101 patients were reviewed from 4634 patients with breast cancer who underwent mastectomies. The chest wall masses were divided into 2 groups depending on their longitudinal diameter (LD; ≤10 and > 10 mm). The US features of the subgroups, depending on their nature (benign and LR), were analyzed and compared. Results: Among 119 masses, 58 (48.74%) were benign masses, and 61 (51.26%) were LR masses. For LR, the mean area under the curve ± SD, sensitivity, and specificity of US were 0.849 ± 0.033, 85.25%, and 84.48% (P < .001), respectively. Among the US characteristics, vascularity, an irregular shape, and a location in deep layers were the top 3 factors related to LR (odds ratios, 4.0, 2.6, and 2.2). To diagnose LR by US, judging the anatomic layer of the locations of masses with an LD of 10 mm or less and the presence of vascularity in masses with an LD of greater than 10 mm were helpful. Conclusions: Ultrasound is a relatively accurate and objective method to differentiate LR from a benign mass after mastectomy with follow‐up. Judging the anatomic layer of the mass location with US likely increases the accuracy of LR diagnosis at an early stage. Abstract : Access the CME test here and search by article title.